Nylon powder for coating and preparation method thereof
By using modified star polymers and nylon resins and other raw materials, combined with high mixer and screw granulation technology, nylon powder for coatings with high mechanical properties and high leveling is prepared, which solves the problem of poor melt flowability of nylon powder and realizes the The product's self-filling pit effect and gloss improve.
Patent Information
- Application Number
- CN202411442874.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art is difficult to improve the melt flowability of nylon powder while maintaining high mechanical properties, and the commonly used method of raising the processing temperature will lead to a decrease in the antioxidant capacity, resulting in defects and hollows on the surface of the product.
Using modified star polymer as melt flow agent, combined with nylon resin, antioxidant and catalyst, nylon powder for coating is prepared by physical mixing of high-mixture machines or deep-cold pulverization after screw granulation, to control particle size and additives Distribute to achieve high leveling and self-filling pit effects.
It achieves high mechanical properties and high leveling nylon powder for coatings. The product has good appearance and gloss, no defects and pits, which improves application prospects.
Smart Images

Figure CN119119860A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nylon powder for coating and a preparation method thereof, belonging to the category of special engineering plastics, and can realize high leveling of powder melting without defects. Background Art
[0002] In the application process of nylon powder as coating and lining, its melt fluidity is generally widely concerned. Powders with poor fluidity will show orange peel effect during melting, and in more serious cases, certain defects and voids will appear on the surface of the product, which greatly affects the appearance and physical protection performance of the powder application products. Therefore, improving the melt fluidity of powder is particularly important for application development. The melt fluidity of powder is closely related to the molecular weight of the product. Generally, powders with small molecular weight have higher melt fluidity, but the lower molecular weight limits the mechanical properties of powder application products, and there will be problems such as leakage of coating and uneven thickness of rotational molding. Therefore, how to maintain good mechanical properties of the product while ensuring good melt fluidity has always been a key research issue in this field.
[0003] During use, the melt fluidity of the powder is generally improved by increasing the processing temperature. However, this method puts the powder's antioxidant capacity under great test because the processing process is generally in a non-nitrogen environment. Therefore, this method will lead to oxidative decomposition of the polymer and reduce the mechanical properties of the material.
[0004] Currently, there are not many related patent methods. It is necessary to find a low-cost and easy-to-implement method to prepare the corresponding powder products to fill the gap in powder products with high melt fluidity and high mechanical properties. Summary of the invention
[0005] The purpose of the present invention is to provide a nylon powder for coating which can realize self-filling pits. The powder maintains good mechanical properties, and the product obtained has good glossiness, no defects and pits, and has great application prospects.
[0006] Another object of the present invention is to provide a method for preparing the self-filling nylon powder for coating.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] A nylon powder for coating comprises the following reaction raw materials: nylon resin, melt flow agent, antioxidant, optional catalyst, optional pigment; wherein the melt flow agent is a modified star polymer, preferably selected from one or more of star polyamide, star polypropylene, and star polyethylene.
[0009] In some specific implementations, based on the total mass of the reaction raw materials, the mass proportions of the components are: melt flow agent 1-3%, antioxidant 0.5-1%, catalyst 0-1%, pigment 0-3%, nylon resin 92-97%.
[0010] In some specific embodiments, the nylon resin is selected from one or more of nylon 12, nylon 612, nylon 11, nylon 1012, and nylon 1010.
[0011] In some specific embodiments, the antioxidant is selected from one or more of hindered amines, cuprous iodides, potassium iodides, hindered phenols, phosphites, and inorganic phosphates;
[0012] In some specific embodiments, the catalyst is selected from one or more of phosphoric acid, phosphorous acid, hypophosphorous acid, sodium hypophosphite, and triphenyl phosphate.
[0013] In some specific embodiments, the preparation process of the modified star polymer comprises the following steps:
[0014] Add polyamide, polyethylene or polypropylene polymer with a molecular weight less than 1000, trimesic acid and a catalyst into a reactor, and perform vacuum reaction for 2-5 hours at a temperature 80-120°C higher than the melting point of the material to obtain a melt of a modified star-shaped polymer. Add the molten material dropwise into a stirred aqueous solution at high temperature to obtain a powdered modified star-shaped polymer.
[0015] In some specific embodiments, the molar ratio of the polymer to trimesic acid is 3.3-3.6:1; the amount of catalyst added accounts for 0.1‰-0.5‰ of the total mass of the polymer and trimesic acid, and the stirring rate of the aqueous solution during feeding is 80-120rpm.
[0016] In some specific embodiments, the pigment is selected from one or more of organic dyes, inorganic pigments or pearlescent pigments.
[0017] On the other hand, the preparation method of the aforementioned nylon powder for coating comprises the following steps: nylon resin, melt flow agent, antioxidant, optional catalyst, pigment are physically mixed by a high mixer or crushed into powder after screw granulation.
[0018] In some specific embodiments, the physical mixing has a mixing speed of 800-1200 rpm and a mixing time of 3-6 min;
[0019] Preferably, the median particle size of the nylon powder for coating obtained by crushing into powder is 50-500 μm;
[0020] More preferably, the powder for coating is prepared by physical mixing, and the particle size range is 50-120 μm; the powder for rotational molding is prepared by screw granulation and crushing, and the particle size range is 200-500 μm.
[0021] Compared with the prior art, the technology and effect of the present invention is to prepare a nylon powder for coating with high mechanical properties and high leveling and self-filling pits, which has corresponding applications in the fields of powder coatings, rotational molding, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an electron microscope photograph of the nylon powder prepared by the physical mixing method in Example 1 of the present invention.
[0023] Figure 2 This is an electron microscope photograph of granulated cryogenically processed nylon powder prepared in Example 2 of the present invention.
[0024] Figure 3 This is an electron microscope photograph of the nylon powder prepared in Comparative Example 1 of the present invention.
[0025] Figure 4 This is a photo of the coating prepared in Comparative Example 1 of the present invention.
[0026] Figure 5 This is a photo of the coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is described in detail below in conjunction with specific embodiments. The embodiments of the present invention are only used to illustrate the present invention, but the protection scope of the present invention is not limited to the following.
[0028] The invention relates to a nylon powder for coating capable of realizing self-filling pits. The powder comprises the following reaction raw materials in percentage by weight based on the total weight of the reaction raw materials: 1-3% of a melt flow agent, 0.5-1% of an antioxidant, 0-1% of a catalyst, 0-3% of a pigment and 92-97% of a nylon resin.
[0029] Wherein, the melt flow agent is a modified star polymer, preferably selected from one or more of star polyamide, star polypropylene, and star polyethylene. Based on the total mass of the reaction raw materials as 100%, the mass proportion of the melt flow agent is 1%, 1.2%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.7%, 3%, etc.
[0030] The modified star-shaped polymer is a modified product of a polymer of polyamide or polyethylene or polypropylene with a molecular weight less than 1000 and trimesic acid, and the specific reaction process is shown in formula (I).
[0031]
[0032] As shown in the reaction equation, it is well known to those skilled in the art that the preparation of the modified star polymer can be achieved by conventional condensation reaction preparation. Specifically, an exemplary method for preparing the modified star polymer comprises the following steps: adding a polymer of polyamide / polyethylene / polypropylene with a molecular weight less than 1000, trimesic acid, and a catalyst to a reactor, vacuuming and reacting for 2-5 hours at a temperature 80-120°C higher than the melting point of the material to obtain a melt of star-shaped polyamide / ethylene / propylene, and dripping the molten material at high temperature into a high-speed stirring aqueous solution through a needle valve to obtain a powdered star-shaped polyamide / ethylene / propylene.
[0033] Wherein, the molar ratio of the polyamide / polyethylene / polypropylene polymer to trimesic acid is 3.3-3.6:1, for example, 3.4:1, 3.5:1, etc., the mass of the catalyst accounts for 0.1‰-0.5‰ of the total mass of the feed, for example, 0.1‰, 0.2‰, 0.3‰, 0.4‰, 0.5‰, etc., and the stirring rate of the water during feeding is 80-120rpm, for example, 80rpm, 90rpm, 100rpm, 110rpm, 120rpm, etc.
[0034] Wherein, the catalyst is a common condensation catalyst, such as phosphoric acid, phosphorous acid, sodium hypophosphite, etc.
[0035] In the present invention, there is no particular limitation on the antioxidant, for example, it can be selected from one or more of hindered amines, cuprous iodides, potassium iodides, hindered phenols, phosphites, and inorganic phosphates, and can be specifically selected from antioxidants commonly used in the art, such as antioxidant 168, antioxidant 1098, antioxidant 626, antioxidant 1010, etc. Based on the total mass of the reaction raw materials being 100%, the mass proportion of the antioxidant is 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.
[0036] In the present invention, the catalyst is one or more of phosphoric acid, phosphorous acid, hypophosphorous acid, sodium hypophosphite, and triphenyl phosphate. Based on the total mass of the reaction raw materials as 100%, the mass proportion of the catalyst is 0, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.
[0037] In the present invention, the pigment is one or more of an organic dye, an inorganic pigment and a pearlescent pigment. The pigments can be selected from pigments commonly used in the art, wherein organic dyes are, for example, phthalocyanine blue, aniline black, oriental black, etc., inorganic pigments are, for example, titanium dioxide, carbon black, titanium yellow, iron red, etc., and pearlescent pigments are, for example, pearlescent 119, pearlescent 113, pearlescent 6117, etc. Based on the total mass of the reaction raw materials as 100%, the mass proportion of the pigment is 0, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.7%, 3%, etc., preferably 1-3%.
[0038] In the present invention, the nylon resin is one or more of nylon 12, nylon 612, nylon 11, nylon 1012, etc. Based on the total mass of the reaction raw materials as 100%, the nylon resin is the remainder excluding the melt flow agent, antioxidant, catalyst, and pigment.
[0039] An exemplary preparation method of the nylon powder for coating of the present invention comprises the following steps: adding nylon resin, melt flow agent, antioxidant, catalyst and pigment into a high-speed mixer for physical mixing or into a screw for melt granulation, and then performing deep cold pulverization after granulation to obtain powder.
[0040] Among them, in the physical mixing method, the speed of the high mixer is 800-1200rpm, such as 800rpm, 900rpm, 1000rpm, 1100rpm, 1200rpm, etc., and the mixing time is 3-6min, such as 4min, 5min, 6min, etc., and high-leveling nylon powder is obtained after mixing; when the screw granulation method is adopted, the extrusion temperature is 190-230°C, and the granulated resin needs to be deep-cold crushed below -140°C in a liquid nitrogen environment, and the crushed powder is dried in a high-temperature oven at 100°C for 2h.
[0041] The present invention can achieve a nylon powder for coating with a median particle size range of 50-500μm, for example, 80μm, 100μm, 150μm, 200μm, 300μm, 400μm, etc., wherein, based on different application scenarios, the coating powder is preferably prepared by physical mixing, with a particle size range of 50-120μm, for example, 60μm, 70μm, 70μm, 90μm, 100μm, 110μm, 120μm, etc.; the rotomoulding powder is preferably prepared by granulation and crushing, with a particle size range of 200-500μm, for example, 200μm, 300μm, 400μm, 500μm, etc.
[0042] The present invention is further explained below by more specific examples, but does not constitute any limitation.
[0043] In this embodiment, the low molecular weight polyethylene used to prepare the star-shaped polyethylene was purchased from APSC in the United States, the low molecular weight polyamide used to prepare the star-shaped polyamide was purchased from Wanhua Chemical, the low molecular weight polyacrylic acid used to prepare the star-shaped polypropylene was purchased from Suzhou Senfida Chemical, and trimesic acid was purchased from Cathay Chemical Co., Ltd. Phosphoric acid, phosphorous acid, and sodium hypophosphite are all commercially available products.
[0044] [Preparation Example 1]
[0045] 1 kg of polyamide oligomer with a molecular weight less than 1000, 59 g of trimesic acid, and 0.5 g of phosphoric acid were added to a reactor, and vacuum reacted at 260°C for 5 hours to obtain a melt of a modified star-shaped polyamide. The melt was added dropwise to an aqueous solution at a stirring speed of 80 rpm at high temperature to obtain a powdered modified star-shaped polyamide.
[0046] [Preparation Example 2]
[0047] 1 kg of low molecular weight polyethylene with a molecular weight of less than 1000, 61 g of trimesic acid and 0.2 g of phosphorous acid were added into a reactor, and the reaction was carried out under vacuum at 200°C for 2 hours to obtain a melt of modified star-shaped polyethylene. The molten material was added dropwise at high temperature into an aqueous solution with a stirring speed of 100 rpm to obtain a powdered modified star-shaped polyethylene.
[0048] [Preparation Example 3]
[0049] 1 kg of low molecular weight polypropylene with a molecular weight less than 1000, 63 g of trimesic acid and 0.3 g of sodium hypophosphite were added into a reactor, and vacuum reacted at 260°C for 3 hours to obtain a melt of modified star-shaped polypropylene. The molten material was added dropwise into an aqueous solution stirred at 120 rpm at high temperature to obtain a powdered modified star-shaped polypropylene.
[0050] [Example 1]
[0051] 9.7 kg of nylon 12 powder, 30 g of antioxidant 168, 30 g of antioxidant 1098, 100 g of star-shaped polyamide powder, 100 g of titanium dioxide, and 40 g of phosphorous acid were added into a high-speed mixer, mixed at 800 rpm for 6 minutes, and discharged after mixing to obtain a nylon powder for coating with high leveling.
[0052] The test data of the obtained powder are shown in Table 1.
[0053] [Example 2]
[0054] 9.2 kg of nylon 11 powder, 50 g of antioxidant 626, 50 g of antioxidant 1010, 300 g of star-shaped polyethylene powder, 100 g of phosphoric acid, and 300 g of phthalocyanine blue dye were added into a screw for mixing and granulation at 190° C. The resin obtained by granulation was deep-cooled to 170° C. by liquid nitrogen, and then crushed into powder. The powder was dried in an oven at 100° C. for 2 hours to obtain a nylon powder for coating with high leveling.
[0055] The test data of the obtained powder are shown in Table 1.
[0056] [Example 3]
[0057] 9.52 kg of nylon 1012 powder, 40 g of cuprous iodide, 40 g of potassium iodide, 200 g of star-shaped polypropylene powder, and 200 g of pearlescent powder were added into a high-speed mixer, mixed at 1200 rpm for 4 minutes, and discharged after mixing to obtain a nylon powder for coating with high leveling.
[0058] The test data of the obtained powder are shown in Table 1.
[0059] [Comparative Example 1]
[0060] 9.7 kg of nylon 12 powder, 30 g of antioxidant 168, 30 g of antioxidant 1098, 100 g of titanium dioxide and 40 g of phosphorous acid were added into a high-speed mixer and mixed at 800 rpm for 6 minutes. After mixing, the material was discharged to obtain a nylon powder for coating with high leveling.
[0061] The test data of the obtained powder are shown in Table 1.
[0062] [Comparative Example 2]
[0063] Add 500ml toluene and 30g triphosgene to a three-necked flask, continue stirring for 1h, transfer the three-necked flask to an ice-fire mixed bath, slowly add 26g 1,2,4,5-cyclohexanetetracarboxylic acid and 1ml N,N-dimethylformamide, continue to react for 2h, transfer to an oil bath, continue to react for 4h at 50°C, and distill under reduced pressure to obtain 1,2,4,5-cyclohexanetetracarboxylic acid chloride. Add 73g lauryl lactam, 400ml deionized water, 100ml toluene, and 168g tetrabutylammonium hydroxide, continue stirring at 40°C for 1h, cool, filter, and vacuum dry to obtain long-chain star-shaped branching agent S5.
[0064] Into the high-pressure reactor, add 10 kg of dodecanediamine salt, 101 g of long-chain star-shaped branching agent S5, 48 g of decanediamine, 97 g of benzoic acid, 1 g of catalyst sodium hypophosphite, 30 g of defoaming agent Carbowax PEG 8000, and 6.7 kg of water. Repeatedly use nitrogen to replace the atmosphere in the reactor and increase the temperature of the material in the reactor until the pressure in the reactor reaches 1.8 MPa. Open the drain valve and continuously drain the water to increase the material temperature to 245°C. After maintaining the pressure for 1.5 hours, reduce the pressure in the reactor to atmospheric pressure, continue the reaction and viscosity increase for 1 hour under slightly positive nitrogen pressure or slightly negative vacuum, discharge the material, pelletize, and deep-cold crush to obtain the corresponding product.
[0065] Table 1 Example test data
[0066] sample Median particle size (um) Relative viscosity Melt index (g / 10mins) Example 1 100 1.63 21 Example 2 340 1.63 25 Example 3 60 1.63 24 Comparative Example 1 95 1.63 17 Comparative Example 2 98 1.56 25
[0067] Performance Testing
[0068] Figures 1 to 3 These are electron microscope photos of Examples 1-2 and Comparative Example 1. It can be seen that Example 1 adopts a mixing method and has a relatively round morphology, and a layer of additives is coated on the surface; Example 2 adopts deep cold crushing to obtain the powder, and its surface morphology is irregular, and because the additives are all added through a screw, there is no additive coating on the surface; Comparative Example 1 is obtained by a mixing method, but due to the lack of a melt flow agent coated on the powder surface, the surface is smoother.
[0069] Figure 4 and Figure 5 This is a comparison chart of the coating effects between Example 1 and Example 1, wherein the coating is prepared by fluidized bed dip coating, wherein nylon powder is fluidized in a fluidized bed at an air pressure of 0.4 MPa, an iron plate at 330°C is immersed in the fluidized bed for dip coating for 2 seconds, and then taken out and naturally cooled to room temperature to obtain the above coating. Figure 4 This is a photo of the coating of Comparative Example 1, which has many depressions and pits. Figure 5 This is a photo of the coating of Example 1. It can be seen that the surface is smooth in the later stage of modification with the additive, and the function of self-filling pits is achieved.
[0070] Table 1 is the test data of the embodiment and the comparative example, wherein based on different application scenarios, there are different particle size methods corresponding to different powder making methods, wherein embodiment 2 is made by cryogenic pulverization, and is mainly used for thicker coating applications such as rotational molding, and its particle size is relatively large, and there is no special requirement for morphology. From the relative viscosity point of view, because its matrix powder is consistent, the viscosity is consistent, but because the addition of auxiliary agents helps the flow of the powder melt, its melt index has obvious differences, and it can be seen that adding more melt flow agents helps the increase of melt fluidity. Comparative Example 2 is a nylon powder made by prior art CN112225891B, because its resin itself is a multi-branch structure, so it can only be prepared by cryogenic method, and the multi-branch structure has the advantage of fluidity under the same viscosity, but the synthesized multi-branch structure is due to the occurrence of cross-linking, so it is impossible to prepare a high viscosity powder. And the present invention can ensure a higher melt index while improving the relative viscosity, thereby achieving the effect of self-filling pits.
[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A nylon powder for coating, characterized in that: The reaction raw materials include: nylon resin, melt flow agent, antioxidant, optional catalyst, and optional pigment; wherein the melt flow agent is a modified star polymer, preferably one or more selected from star polyamide, star polypropylene, and star polyethylene.
2. The nylon powder for coating according to claim 1, characterized in that: Based on the total mass of the reaction raw materials, the mass proportion of each component is: melt flow agent 1-3%, antioxidant 0.5-1%, catalyst 0-1%, pigment 0-3%, nylon resin 92-97%.
3. The nylon powder for coating according to claim 1 or 2, characterized in that: The nylon resin is selected from one or more of nylon 12, nylon 612, nylon 11, nylon 1012, and nylon 1010.
4. The nylon powder for coating according to any one of claims 1 to 3, characterized in that: The antioxidant is selected from one or more of hindered amines, cuprous iodides, potassium iodides, hindered phenols, phosphites, and inorganic phosphates.
5. The nylon powder for coating according to any one of claims 1 to 4, characterized in that: The catalyst is selected from one or more of phosphoric acid, phosphorous acid, hypophosphorous acid, sodium hypophosphite, and triphenyl phosphate.
6. The nylon powder for coating according to any one of claims 1 to 5, characterized in that: The preparation process of the modified star polymer comprises the following steps: Add polyamide, polyethylene or polypropylene polymer with a molecular weight less than 1000, trimesic acid and a catalyst into a reactor, and perform vacuum reaction for 2-5 hours at a temperature 80-120°C higher than the melting point of the material to obtain a melt of a modified star-shaped polymer. Add the molten material dropwise into a stirred aqueous solution at high temperature to obtain a powdered modified star-shaped polymer.
7. The nylon powder for coating according to claim 6, characterized in that: The molar ratio of the polymer to trimesic acid is 3.3-3.6:1; the amount of catalyst added accounts for 0.1‰-0.5‰ of the total mass of the polymer and trimesic acid, and the stirring rate of the aqueous solution during feeding is 80-120rpm.
8. The nylon powder for coating according to any one of claims 1 to 6, characterized in that: The pigment is selected from one or more of organic dyes, inorganic pigments or pearlescent pigments.
9. The method for preparing nylon powder for coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: The nylon resin, melt flow agent, antioxidant, optional catalyst and pigment are physically mixed by a high mixer or crushed into powder after being granulated by a screw.
10. The preparation method according to claim 9, characterized in that: The mixing speed of the physical mixing is 800-1200 rpm, and the mixing time is 3-6 min; Preferably, the median particle size of the nylon powder for coating obtained by crushing into powder is 50-500 μm; More preferably, the powder for coating is prepared by physical mixing, and the particle size range is 50-120 μm; the powder for rotational molding is prepared by screw granulation and crushing, and the particle size range is 200-500 μm.
Citation Information
Patent Citations
A method for preparing a long-chain star-shaped branching agent and a high-flow, high-crystallinity long-carbon-chain star-shaped polyamide.
CN112225891B
Process for preparing particles based on a thermoplastic polymer and powder thus obtained
CN101421355A
Powder coating composition, and preparation method and application thereof
CN110343445A
Method for improving processing fluidity of nylon 66 composite material by using hyperbranched polyamide
CN117532794A
Powder paint composition
WO2008031589A2
Cited By
Nylon powder as well as preparation method and application thereof
CN121471698A
High color saturation high temperature resistant polyamide powder coating and preparation method
CN123026938A
